EXPERIMENTAL AND FINITE ELEMENT ANALYSIS REGARDING THE INFLUENCE OF FRICTION CONDITIONS ON MATERIAL FLOW IN METAL FORMING PROCESSES - POP, M.; FRUNZA, D. (Studia Universitatis Babeș-Bolyai Physica, 2015)
When friction occurs between tool and workpiece, surface expansion and high normal pressure between work piece and die, leads to adhesions(cold-weld), abrasion of die and work material. To reduce the friction, it requires a suitable lubricant. In the present work different lubricated condition were tested in the extrusion process of lead. The influence of lubricated conditions on the material flow and process parameters were determined. Experimental values were compared with simulation.